Processi di visualizzazione poetica: descrizione e immaginazione nella critica di danza del XIX secolo - Christina Thurner (Danza e Ricerca, 2014)
This essay addresses the interest in the discourse of dance criticism within the French feuilleton of the 19th Century. It explores poetical techniques of writing with regard to and on examination of the perception of romantic ballet. The author of the essay argues that critics as Théophile Gautier and Jules Janin created and cultivated an emphatic style of criticism, which can be described as a transposition of the subjective view / imagination of the observer into poetic language. These discoursive practices became significant and paradigmatic – also in relation to the perception of dance till this day.